PRAMUKA DALAM MEMBENTUK KARAKTER KEBANGSAAN SEBAGAI BAGIAN CIVIC DISPOSITION SISWA DI MTS NURUL MA’ARIF 1 DEDAI - Sapto Purnomo; Juri Juri; Septha Suseka; Edo Abdullah (STKIP Persada Khatulistiwa Sintang, 2023)
Character education is an important part of education. The purpose of this study is to describe scout activities in shaping national character as part of the civic disposition of students at MTs Nurul Ma'arif 1 Dedai. This research uses qualitative descriptive method with descriptive research form. Data collection uses observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and conclusions. From the results of this study found: 1). The strategy used in the implementation of extracurricular scouts is good. 2). Scout extracurricular activities at MTs Nurul Ma'arif 1 Dedai play an important role in shaping national character as part of civic disposition, namely shaping students' religious, honest and disciplinary values. 3). The obstacles faced by the coach are different student characters, facilities and infrastructure supporting scout activities and less optimal time in scout activities. Keywords: Scout, National Character, Civic Disposition.